PERFORMA PERTUMBUHAN IKAN KAKAP (Lates calcarifer) dengan UKURAN PAKAN yang BERBEDA di PT. SURI TANI PEMUKA (STP) UNIT MARINE FISH POND SOBO, BANYUWANGI - Febrian, Navila Eka (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
This study aims to examine the effect of feed size on the growth of barramundi (Lates calcarifer) cultivated at PT Suri Tani Pemuka, Banyuwangi. The experiment utilized two feed sizes, small (7 mm) and large (20 mm), administered twice daily. The results showed that small-sized feed led to a higher average weight gain of 3.90 grams compared to large-sized feed, which only achieved 3.43 grams. Small feed, with a higher protein content (50-52%), is easier to digest, promoting better nutrient absorption efficiency and optimal fish growth. This study highlights the importance of selecting the appropriate feed size to enhance the efficiency of barramundi cultivation. Further research is recommended to explore various feed sizes and types as well as to evaluate the impact of water quality on fish growth.